Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/foods12203731
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Polysaccharide Binders on the Quality Characteristics of Plant-Based Patties

Jong-Hyeon Han,
Dong-Hyun Keum,
Seong-Joon Hong
et al.

Abstract: Polysaccharides have been used in the production of plant-based meat analogs to replicate the texture of real meat. However, there has been no study that comprehensively compares the effects of different polysaccharides, and a limited number of polysaccharides have been evaluated. Thus, we aimed to identify the most suitable polysaccharide and concentration for plant-based patties. Plant-based patties were manufactured by blending different concentrations (0%, 1%, and 2%) of six polysaccharides with other ingr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…It was found that these PNPs greatly increased fibers' cohesiveness and created a more porous structure, which provides a new approach for the largescale production of plant-based meat analogs. J. H. Han et al (2023) compared the effects of six polysaccharides on the quality characteristics of plant-based patties and found the 2% κ-carrageenan addition offered a feasible way of crafting plant-based meat analogs due to its potential to enhance texture and flavor. As mentioned above, PNPs as functional additions can directly add to plant protein to enhance the texture and sensory evaluation of plantbased meat, which improves consumers' acceptance of this cultured meat.…”
Section: Plant-based Meatmentioning
confidence: 99%
“…It was found that these PNPs greatly increased fibers' cohesiveness and created a more porous structure, which provides a new approach for the largescale production of plant-based meat analogs. J. H. Han et al (2023) compared the effects of six polysaccharides on the quality characteristics of plant-based patties and found the 2% κ-carrageenan addition offered a feasible way of crafting plant-based meat analogs due to its potential to enhance texture and flavor. As mentioned above, PNPs as functional additions can directly add to plant protein to enhance the texture and sensory evaluation of plantbased meat, which improves consumers' acceptance of this cultured meat.…”
Section: Plant-based Meatmentioning
confidence: 99%